Implementasi Penguatan Kapasitas Kerjasama Indonesia-United States Agency For International Development (USAID) Dalam Bidang Pendidikan - Dewi Romantika Tinambunan; Esra Natasya Sitepu; Ivana Theo Philia; Jekson Saragih; Laras Sati Sintania; Ture Ayu Situmeang; Isnaniah Isnaniah (Politeknik Kampar, 2023)
International cooperation is a form of cooperation carried out by a country with other countries across its territorial borders. The aim of cooperation is to meet the needs of the country. This research is entitled